Style and quality of life of waste collectors - Flávia Mendes da Silva; Paulo Henrique Alves de Sousa; Renata Cristina da Penha Silveira (Universidade Federal de Goias, 2017)
The study aimed to analyze the style and quality of life of waste collectors and, to compare its respective domains. A cross-sectional and analytical study, conducted with 43 waste collectors of an inner city in Minas Gerais state. We used a form containing socio-economical and demographic data, WHOQOL-Bref and the Estilo de Vida Fantástico - EVF (FANTASTIC Lifestyle Assessment - Brazilian version). The results showed that there was a significant association between the results from the WHOQOL-Bref and EVF (p<0.05), indicating that higher quality of life scores are associated with better lifestyles. Despite the adverse conditions inherent from work executed by the collectors and its external causes, like the weather, odor, weight, physical effort, and low salaries, there was a satisfactory assessment for questions composing quality of life and lifestyle. From the exposed, it was evident that the work, health, quality of life and lifestyle are related and determine the worker's profile in their subjective life, as well as, in their work life.